Prognostic impact of previous intraarterial treatment in patients with hcc treated with sorafenib. (March 2023) - Stefanini, B.; Ielasi, L.; Pressiani, T.; Trevisani, F.; Sacco, R.; Gardini, A. Casadei; Magini, G.; Di Costanzo, G.G.; Granito, A.; Tovoli, F.; Piscaglia, F.
Abstract : Introduction and Aim: Hepatocellular carcinoma (HCC) can be treated with different treatment options, TACE is among the most effective options in patients at intermediate stage (BCLC B), however failure rate and its risk of liver function impairment are also well-known. Depending on local expertise patients belonging to BCLC-B stage are often treated with multiple loco-regional treatments even if unsuccessful rather than receive systemic therapy upfront. In this study we aimed to evaluate the impact of previous TACE on patients who received Sorafenib. Method: Multicentric retrospective study involving patients who received Sorafenib between January 2010 and December 2018 in 6 different Italian hospitals. We included 668 patients from the ARPES database, 116 patients (17.6%) received more than two intraarterial treatments, 129 received only one treatment and 102 received 2 different TACE, while the remaining part of the population did not receive any TACE. We used a Cox-regression analysis to find predictors of survival. Results: No changes in term of OS were found between patients who received >2 TACE (mOS 11.1 months) and patients who received two or less (mOS 12.4), a closer look to the curve shows how after the first 12 months there is a sustained separation between these groups. Thus we stratified our population according to response to sorafenib, median OS in Non-responder was not affected from the number of TACE they received, whereas in the Responder group patients who received ≤2 TACE had a significant prolonged median OS than patients who received ≥3 TACE (22.6 months vs 15.6 months, p=0.04). This was confirmed in the multivariate analysis where TACE was an independent predictor of mortality with an hazard ratio of 1, 547 (p= 0, 016). Conclusion: This study demonstrates how having received more than two TACE is an independent risk factor for mortality in patients who respond to Sorafenib.